Investigation on the different types of materials of joining for automotive panel - Mohamad Suhaimi, Samsudin (2007)
The technique of joining two or more different panels is called as Tailor Welded Blank (TWB). The panels could vary in thicknesses, grades or coating and joined by the mean of welding. This technique is widely being used by automotive manufacturer in the world because of the abundant benefits. But, Malaysian automotive manufacturers are still lack of this advancement. Hence, this project endeavors to build a platform for the industries by pioneering researches in this area. So, the purpose of the project is to find the best joining materials to be integrated into TWB by comparing each specimen and then proposed the potential TWBs to be used as automotive panel specially aimed for door inner panel for the hinge section. Base metals of 0.7mm thick from SPCC and SPCEN grades and 1.2 mm thick from SPHC, SAPH 370 and SGACC grades are chosen to be the joining materials and laser welding is chosen to be the method for joining. Each specimen will be tensile tested in order to find the properties that influence the weldability, formability and drawability of the TWBS. Then the data obtained will be analyze by distinguishing them into several sets of parameter to determine the significant factor and thus, decided the best material combination as the potential Tailor Welded Blanks.